(untitled) (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Diarrhea is a condition of defecation with a different frequency than usual, namely more often or more than 3 times in one day, with a soft or liquid consistency or even just water. Diarrhea is caused by viral or bacterial agents that infect the digestive tract. Diarrhea can cause dehydration and even death if not treated properly. This research is to determine the effect of education through audio-visual media on mothers’ knowledge about diarrhea in toddlers in Lima in Megaria Hamlet Pelauw Village 2024. This research uses quantitative research with a pre-experimental method with a one group pre-test and post-test design approach. The population in this study was 45 mothers who had toddlers, while the sample in this study was 45 mothers who had toddlers. The sampling technique uses total sampling. The research instrument uses a questionnaire in the form of statements. The analysis used is the Wilcoxon test. Results: analysis of the influence of education using audio visual media on mothers’ knowledge about diarrhea in toddlers in Lima Megaria hamlet in Pelauw village in 2024 from the results of the Wilcoxon Test. Respondents’ knowledge increased to 45 respondents. The research results showed that there was a significant influence after respondents were given education or Ha received it, meaning that there was an influence of education using audio-visual media on mothers’ knowledge about diarrhea in toddlers in Lima in Megaria hamlet Pelauw village in 2024. Keywords: Education, Audio Visual, Diarrhea, Maternal